Boundary objects and beyond working with Leigh Star - Bowker, Geoffrey C.; Timmermans, Stefan 1968-; Clarke, Adele E. 1945-; Balka, Ellen 1956- (The MIT Press, 2015)
Susan Leigh Star (1954-2010) was one of the most influential science studies scholars of the last several decades. In her work, Star highlighted the messy practices of discovering science, asking hard questions about the marginalizing as well as the liberating powers of science and technology. In the landmark work Sorting Things Out, Star and Geoffrey Bowker revealed the social and ethical histories that are deeply embedded in classification systems. Star's most celebrated concept was the notion of boundary objects: representational forms - things or theories - that can be shared between different communities, with each holding its own understanding of the representation. Unfortunately, Leigh was unable to complete a work on the poetics of infrastructure that further developed the full range of her work. This volume collects articles by Star that set out some of her thinking on boundary objects, marginality, and infrastructure, together with essays by friends and colleagues from a range of disciplines - from philosophy of science to organization science - that testify to the wide-ranging influence of Star's work. Contributors Ellen Balka, Eevi E. Beck, Dick Boland, Geoffrey C. Bowker, Janet Ceja Alcal , Adele E. Clarke, Les Gasser, James R. Griesemer, Gail Hornstein, John Leslie King, Cheris Kramarae, Maria Puig de la Bellacasa, Karen Ruhleder, Kjeld Schmidt, Brian Cantwell Smith, Susan Leigh Star, Anselm L. Strauss, Jane Summerton, Stefan Timmermans, Helen Verran, Nina Wakeford, Jutta Weber
"Based on the Conference: A Celebration of Susan Leigh Star: Her Work and Intellectual Legacy, University of California, San Francisco (UCSF), September 2011"- (Copyright page). - Includes bibliographical references and index
Keywords: Star, Susan Leigh -- 1954-2010; Cognition; Communication / Social aspects; Information technology / Social aspects; Interdisciplinary research; Knowledge, Sociology of; Social ecology; Gesellschaft; Soziologie; Electronic books; Festschrift